XIAP protein is induced by placenta growth factor (PLGF) and decreased during preeclampsia in trophoblast cells. (October 2014) - Arroyo, Juan; Price, Mathew; Straszewski-Chavez, Shawn; Torry, Ronald J.; Mor, Gil; Torry, Donald S.
Abstract Increased trophoblast apoptosis has been implicated in pregnancies complicated by fetal growth restriction and preeclampsia (EC). We investigated placenta growth factor (PLGF) signaling during trophoblast apoptosis in culture and X-linked inhibitor of apoptosis protein (XIAP) and apoptosis inducible factor (AIF) in the preeclamptic placenta at term was determined. Primary trophoblasts were isolated and serum starved to induce apoptosis. Placenta growth factor was added and apoptosis markers were determined. Term preeclamptic placentae were homogenized and the levels of XIAP and XAF1 protein were assessed. In the absence of serum, primary cultures of term trophoblast showed a 5-fold increase in apoptosis as determined by annexin V binding. The increase in apoptosis induced by serum deprivation was caspase-independent and could be significantly reduced (p < 0.02) with the addition of 10 ng/ml rh PLGF to the media. In addition, PLGF mediated increased protein expression of the anti-apoptotic XIAP as well as decreased expression of the pro-apoptotic AIF in the primary trophoblast. In preeclamptic placenta, we determined the concomitant decrease in XIAP RNA as well as decreased expression of the phosphorylated XIAP protein. These results were coupled with increased levels of the pro-apoptotic protein XAF1. Our results suggest that PLGF protects trophoblast from caspase independent apoptosis in culture by increasing XIAP production and deceasing AIF. Also, our data suggests that decreased activation of XIAP and increased XAF1 could be factors associated with the increased placental apoptosis observed in the preeclamptic placenta at term.